Analisis Kritis Konstruksi Narasi Media dan Persepsi Mahasiswa Terhadap Pilpres 2024: Studi Kasus di Universitas Madura - Fredy Yunanto; Mohammad Rudiyanto; Ria Kasanova; Alfia Alfia (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research examines a critical analysis of the formation of media narratives and student perspectives around the 2024 Presidential Election using a case study at Madura University. In a dynamic democratic framework, the media significantly influences public opinion through framing and agenda setting. This research employs a qualitative methodology using in-depth interviews to investigate students' impressions of existing media narratives. The results showed that print and digital media frame political topics in ways that can influence students' political perspectives. Although some students understand the influence of these narratives, different levels of media literacy affect their susceptibility to deception. This study underlines the importance of higher education in improving political awareness and media literacy among young people. Consequences of this study include contributions to political and communication theory, as well as recommendations for improving media literacy in educational institutions. The constraints of this study, including the limited sample coverage, underscore the need for further research to understand the influence of media narratives on different groups of society. This research aims to provide insights to policymakers and academics regarding political and media education.